Experimental and numerical study on the prefabricated double L-shaped beam-column joint with triangular stiffener. (15th June 2023) - Yang, Zhaoyuan; Cao, Wanlin; Qiao, Qiyun; Zhang, Jianwei
Abstract: This study proposes an innovative prefabricated double L-shaped beam-column joint with triangular stiffener (double L-shaped joint) for low-rise residential buildings. The double L-shaped joint consists of the L-shaped connector with triangular stiffener, web side plate connection, H-shaped beam, and concrete-filled lightweight steel tube (CFLST) column or square hollow steel tube (SHS) column. Twelve double L-shaped joints are manufactured and experimented. The design parameters include the column types (CFLST or SHS), triangular stiffener height, perforated end plate (with or without), and the web side plate connection (with or without). In addition, the failure modes, hysteretic performances, ultimate capacity, stiffness degradation, deformation capacity, energy dissipation, and strain responses of joint specimens are analyzed. The experimental results show that the failure modes include steel tube local buckling, weld cracking, and bolts fracture in the area of the L-shaped connector. The ultimate moment of the CFLST column joints rises from 4.53% to 13.05% compared to the SHS column joints, while the initial stiffness increases from 2.16% to 26.46%. The perforated end plate grows at the ultimate moment, but the ductility index reduces. The initial stiffness and deformation capacity of the specimens without a web side plate connection decreases significantly. The finite element model is developed, and the numerical simulation is conducted. The experimental results are consistent with failure modes and bending moment versus rotation angle curves obtioned by numerical simulation. Highlights: An innovative double L-shaped beam-column joint was proposed in this study. Seismic behavior of double L-shaped point was experimentally and numerically investigated. Seismic behavior of joint was improved with the increase of triangular stiffener height.